Filtration and Breathability of Nonwoven Fabrics Used in Washable Masks - Thomas W. Bement; David J. Downey; Ania Mitros; Rebecca Lau; Timothy A. Sipkens; Jocelyn Songer; Heidi Alexander; Devon Ostrom; Hamed Nikookar; Steven N. Rogak (Aerosol and Air Quality Research)
Abstract We consider fabrics that can improve upon the performance of the widespread all-cotton mask, and examines the effect of layering, machine washing and drying on their filtration and breathability. Individual materials were evaluated for their quality factor, Q, which combines filtration efficiency and breathability. Filtration was tested against particles 0.5 µm to 5 µm aerodynamic diameter. Nonwoven polyester and nonwoven polypropylene (craft fabrics, medical masks, and medical wraps) showed higher quality factors than woven materials (flannel cotton, Kona cotton, sateen cotton). Materials with meltblown nonwoven polypropylene filtered best, especially against submicron particles. Subsequently, we combined high performing fabrics into multi-layer sets, evaluating the sets’ quality factors before and after our washing protocol, which included machine washing, machine drying, and isopropanol soak. Sets incorporating meltblown nonwoven polypropylene designed for filtration degraded significantly post-wash in the submicron range where they excelled prior to washing (Q > 50 kPa−1 at 1 µm, respectively, degraded to Q < 10 post-wash). Washing caused lesser quality degradation in sets incorporating spunbond non-woven polypropylene or medical wraps (Q = 12 to 24 pre-wash, Q = 8 to 10 post-wash). Post-wash quality factors are similar for all multi-layer sets in this study, and higher than Kona quilting cotton (Q = 6). Washed multi-layer sets filtered 12% to 42% of 0.5 µm, 27% to 76% of 1 µm, 58% to 96% of 2.8 µm, and 72% to 100% of 4.2 µm. The measured filtration and pressure drop of both the homogeneous and heterogeneous multi-layer fabric combinations agreed with the estimations from a model assuming layers filter independently. Further examination of selective nonwovens showed that IPA degraded their filtration, while washing and drying produced variable effects on their filtration. Variability in filtration and pressure drop was observed in and across Filti samples.